2016
DOI: 10.1038/srep37792
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary conserved interaction between the Gcm transcription factor and the SF1 nuclear receptor in the female reproductive system

Abstract: NR5A1 is essential for the development and for the function of steroid producing glands of the reproductive system. Moreover, its misregulation is associated with endometriosis, which is the first cause of infertility in women. Hr39, the Drosophila ortholog of NR5A1, is expressed and required in the secretory cells of the spermatheca, the female exocrine gland that ensures fertility by secreting substances that attract and capacitate the spermatozoids. We here identify a direct regulator of Hr39 in the spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…Multiple factors have been linked to sperm longevity, including ions, sugars, pH, antioxidants, and enzymes for energy metabolism [13][14][15][16][17][18]. However, the current understanding of biochemical and physiological processes within the spermathecae is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors have been linked to sperm longevity, including ions, sugars, pH, antioxidants, and enzymes for energy metabolism [13][14][15][16][17][18]. However, the current understanding of biochemical and physiological processes within the spermathecae is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that dynamic Notch signaling regulates binary fate determination in Drosophila spermathecal lineage (Shen and Sun, 2017). Drosophila spermatheca is a class-III insect gland containing ∼80 secretory units that produce essential secretions for sperm storage and ovulation (Filosi and Perotti, 1975;Schnakenberg et al, 2011;Sun and Spradling, 2013;Cattenoz et al, 2016). Lineage-tracing experiments show that spermathecal gland precursors (P0) in the genital imaginal disc proliferate to give rise to one secretory unit precursor (SUP) and one lumen epithelial precursor (LEP) around 26 hours (h) after puparium formation (APF; Sun and Spradling, 2012;Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely true in other insect species ( Shaw et al 2014 ). In addition, glandular secretions from spermathecae and parovaria regulate ovulation and egg laying ( Schnakenberg et al 2011 ; Sun and Spradling 2013 ; Cattenoz et al 2016 ). Although the exact identities of the secreted products regulating sperm and ovulation are unknown, it is clear that secretions through the canonical protein secretory pathway are required for sperm storage but not ovulation ( Sun and Spradling 2013 ).…”
mentioning
confidence: 99%
“…The sex determination cascade activates the runt-domain transcription factor Lozenge (Lz) in these primordial cells, which is essential for gland formation ( Anderson 1945 ; Chatterjee et al 2011 ; Sun and Spradling 2012 ). NR5A-family nuclear receptor Hr39 regulates the proliferation, survival, and protrusion of these primordial cells during early pupae development; Hr39 expression is likely regulated by the transcription factor Glial cell missing ( Allen and Spradling 2008 ; Sun and Spradling 2012 ; Cattenoz et al 2016 ). Precursor cells except those at the middle region of the spermathecal head continue to express Lz and differentiate into epithelia cells (ECs) to form adult spermathecal lumen and duct.…”
mentioning
confidence: 99%